Antibacterial Activity of Chayote (Sechium edule Swartz) Squash Extracts and Their Phytochemical Constituents - Sulistiyani, Nur Indah; Ainurrofiq, Ahmad; Suryanti, Venty (Pusat Penelitian dan Pengembangan Bioteknologi dan Biodiversitas (P3BB) LPPM UNS, 2022)
Antibacterial activity of chayote (Sechium edule Swartz) squash extracts against pathogenic bacteria has been evaluated. Dried chayote squash powder was extracted using methanol which was then extracted successively using hexane, chloroform, ethyl acetate, and butanol. The antibacterial activities of the extracts were tested by the hole diffusion method. Methanol extract of chayote squash had antibacterial activity against Staphylococcus aureus, Bacillus subtilis, Pseudomonas aeruginosa, and Escherichia coli but did not have antibacterial activity against Enterobacter aerogenes, Shigella dysenteriae, and Salmonella typhi. Ethyl acetate extract had the highest antibacterial activity against P. aeruginosa and E. coli. The ethyl acetate extract contains phenolics, condensed tannins, flavonoids, and terpenoids. The ethyl acetate extract had a MIC of 50 mg/ml for S. aureus, B. subtilis, P. aeruginosa, and E. coli. Different bioactivities of tested extracts were found due to various chemical compositions of extracts as a result of different polarities of the solvent.